Decision strategies and influencing factors of international students’ university entrance in Japan - Wu, Qinpeng; Ishii, Hidetoki (Journal of International Students, 2025)
International students need to consider multiple constraints simultaneously in their decision-making for university admission. However, most of them face the problems of lacking knowledge of the decision-making process and making decisions on where to go before they become familiar with the university. This study focused on international students who planned to study at a Japanese university, proposed the factors influencing career decision strategies, and examined each factor via exploratory factor analysis. Based on the exploratory factor analysis results, we construct a decision-making model and employ SEM analysis to investigate how international students in Japan overcome constraints and ultimately make decisions, identifying common behavioral patterns among them.